Chronological Change of Right Ventricle by Chronic Intermittent Hypoxia in Mice. Issue 8 (20th June 2017) - Cho, Hyung-Ju; Heo, Woon; Han, Jung Woo; Lee, Yong Hyuk; Park, Jin Myung; Kang, Min Jung; Yoon, Joo-Heon; Lee, Min Goo; Kim, Chang-Hoon; Kim, Joo Young
Abstract: Study Objective: No studies have investigated sequential changes in the heart on magnetic resonance imaging (MRI), along with observation of functional lung phenotypes and genetics, over the duration of chronic intermittent hypoxia (CIH). We investigated chronological changes in heart and lung phenotypes after CIH using a mouse model to provide new insights into the pathophysiology of sleep apnea-induced cardiovascular disease. Methods: C57BL/6J adult male mice were randomized to 4 or 8 weeks of CIH. Cardiac cine-MRI images were analyzed to assess functional parameters of right ventricle (RV). Histopathological features of myocytes and pulmonary vessels, as well as genes involved in the endothelin (ET) system, were investigated. Results: Function of the RV reduced significantly at 4 weeks and continuously decreased following another 4 weeks of CIH, although the rate of decrease was attenuated. Notably, persistence of reduced ejection fraction and end-systole RV wall thickness (WT) and increases in the ET system of the lungs and blood strongly implied the development of pulmonary hypertension after 8 weeks of CIH. Conclusions: RV dysfunction with reduced end-systole RV WT could be a late phenotype in long-standing CIH and possibly also in obstructive sleep apnea.